ISOLATION OF MEDICAL STUDENTS: COMMUNICATION BARRIER AND ITS EFFECT ON CAREER - Gul, Mahwish; Rasool, Ahsan; Khalid, Laiba Binte; Rasool, Maleeha; Khan, Farmanullah; Ayub, Muhammad; Marwat, Salim (Journal of Ayub Medical College Abbottabad, 2012)
Background: Communication barriers affect student-student interaction and student-patient interaction. This study is aimed at exploring the social, cultural and academic spheres where medical students feel getting isolated. Method: Questionnaire based cross-sectional survey was undertaken at Ayub Medical College, Abbottabad in the month of July, 2013. Cluster sampling technique was employed. Results: Linguistic problems in the college greatly affected medical students. Female medical student are comparatively more affected. These problems were less common in 1st year and most common in 3rd year where clinical classes are started. There are distinct gender based problems in communicating among male and female student with as many as 37.2% reported feeling difficulty in communicating with students of opposite gender. However this difficulty in communication gradually faded on proceeding from 1st year towards final year. About frank interaction with opposite gender, 65.9% students felt that society had negative impact upon it. While communicating with patients of opposite gender, almost a quarter of students (27.3%) reported facing difficulties, 56.9% students reported to have abject apathy towards the colleagues of opposite gender. Conclusion: Linguistic issues, gender discrimination, negative impact of society and lack of concern for fellow colleagues is affecting student-student interaction and student-patient interaction. There is need to create student friendly environment. Keywords: Linguistic issues, gender discrimination, medical students